Trauma quality indicators: internationally approved core factors for trauma management quality evaluation - Federico Coccolini; Yoram Kluger; Ernest E. Moore; Ronald V. Maier; Raul Coimbra; Carlos Ordoñez; Rao Ivatury; Andrew W. Kirkpatrick; Walter Biffl; Massimo Sartelli; Andreas Hecker; Luca Ansaloni; et al. (World Journal of Emergency Surgery)
Abstract Introduction Quality in medical care must be measured in order to be improved. Trauma management is part of health care, and by definition, it must be checked constantly. The only way to measure quality and outcomes is to systematically accrue data and analyze them. Material and methods A systematic revision of the literature about quality indicators in trauma associated to an international consensus conference Results An internationally approved base core set of 82 trauma quality indicators was obtained: Indicators were divided into 6 fields: prevention, structure, process, outcome, post-traumatic management, and society integrational effects. Conclusion Present trauma quality indicator core set represents the result of an international effort aiming to provide a useful tool in quality evaluation and improvement. Further improvement may only be possible through international trauma registry development. This will allow for huge international data accrual permitting to evaluate results and compare outcomes.